The perception of midwives on the implementation of South Africa's maternal care guidelines in postnatal health in KwaZulu-Natal Province: A qualitative study - Okeke, Ngozichika Obiageli; Ngunyulu , Roinah (Universitas Airlangga, 2025)
Introduction: Midwives are essential to the advancement of maternal and postnatal health in any society. Despite this importance, postnatal care for mothers should follow basic guidelines that midwives must adhere to. As key members of the medical team, midwives are crucial collaborators in implementing postnatal care guidelines, which may help lower preventable deaths and improve quality of life. Objectives: This study investigated midwives' perspectives on implementing maternal care standards following childbirth at a district hospital in KwaZulu-Natal, South Africa. Methods: A descriptive qualitative design was used with 25 licensed midwives: 17 attending midwives and 8 midwifery managers who were purposively selected from the public sector. Data were gathered through interviews and field recordings. The study lasted 16 weeks, and interviews ranged from 20 to 45 minutes. Data were transcribed and analyzed thematically using Braun and Clarke's approach. Results: The study found that despite the indispensable role of midwives, maternal care standards did not adequately meet postnatal health outcomes. This was attributed to workforce and resource shortages, inadequate training and support, ineffective communication, supervision, and monitoring, as well as poor system coordination and capacity building. Policy guideline revision is necessary to address these challenges and discrepancies in the formulation and implementation of guidelines within the healthcare sector with the largest burden on postnatal health. Conclusion: Midwives require training to increase their awareness and competence in implementing maternal care guidelines. Both legislators and healthcare providers should give careful consideration to implementing South African maternal care standards in postnatal health. Keywords: midwives' perception; postnatal health; south africa maternal care guidelines